2021
DOI: 10.1128/msphere.00661-21
|View full text |Cite
|
Sign up to set email alerts
|

Heliorhodopsin Evolution Is Driven by Photosensory Promiscuity in Monoderms

Abstract: Heliorhodopsins are enigmatic, novel rhodopsins with a membrane orientation that is opposite to all known rhodopsins. However, their cellular and ecological functions are unknown, and even their taxonomic distribution remains a subject of debate.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 75 publications
(107 reference statements)
0
24
0
Order By: Relevance
“…Bulzu and colleagues identified MORN (Membrane Occupation and Recognition Nexus, PF02493) repeat and zinc ribbon proteins (Pfam domain zinc_ribbon_4) at the N-termini of certain heliorhodopsins; these proteins were modeled to be fused to heliorhodopsins. They suggested that the proteins fused to heliorhodopsins may be related to the PPI or an indication of the role of zinc in possible downstream signaling [ 21 ]. Bulzu and colleagues and Chazan and colleagues also suggested diverse functions resulting from the relationship between heliorhodopsins and neighboring genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulzu and colleagues identified MORN (Membrane Occupation and Recognition Nexus, PF02493) repeat and zinc ribbon proteins (Pfam domain zinc_ribbon_4) at the N-termini of certain heliorhodopsins; these proteins were modeled to be fused to heliorhodopsins. They suggested that the proteins fused to heliorhodopsins may be related to the PPI or an indication of the role of zinc in possible downstream signaling [ 21 ]. Bulzu and colleagues and Chazan and colleagues also suggested diverse functions resulting from the relationship between heliorhodopsins and neighboring genes.…”
Section: Resultsmentioning
confidence: 99%
“…Heliorhodopsin photocycle was slow, a feature that is widespread in sensory rhodopsins (SRs). Accordingly, Pushkarev and colleagues suggested that heliorhodopsins function as a distinct type of signaling photoreceptors similar to SRs [ 17 ], whereas the N-termini of heliorhodopsins might participate in enzyme function [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fosmid had low sequence similarity to known rhodopsins, which attributed to the lack of detection of HeRs in typical bioinformatic searches 1 . Now, 22 more HeRs have been discovered through pigmented E. coli screens 3 , 4 , and over 400 unique HeR sequences have been found from homology searches of whole genomes from microorganisms 5 , 6 . It turns out that HeRs comprise a large and diverse group of rhodopsins.…”
mentioning
confidence: 99%
“…Moreover, HeRs can be found in psychrophiles, mesophiles, and hyperthermophiles that live in various temperature environments 1 , 8 . Interestingly, bioinformatic analysis revealed that HeRs are found in gram positive bacteria and are largely absent in gram negative bacteria 6 , 8 , although this taxonomic distribution in monoderms and diderms was somewhat debated 5 .
Figure 1 Phylogenetic tree of microbial rhodopsins with representative HeRs and type I rhodopsins.
…”
mentioning
confidence: 99%
See 1 more Smart Citation